Coral fish condition in the waters of Pare-Pare Bay and Awerange Bay South Sulawesi - SUHARYANTO SUHARYANTO; UTOJO UTOJO (Society for Indonesian Biodiversity, 2007)
Observation on fish coral condition was conducted in the waters of Pare-Pare and Awerange Bay, South Sulawesi, on October and November 2004, using scuba diving set and under water writting tools. Monitoring of fish coral conditions were conducted in 7 m depths up to 100 m length of shore line were observed in four stations of diving, two stations in Pare-pare Bay and two stations in Awerange Bay using â€œsencus visual of Line Intercept Transectâ€ method. The result showed that in the waters of Pare-Pare Bay were not found fish coral, just pelagic fish were found, meanwhile in the waters of Awerange Bay, fish coral found as much as 17 families and 46 specieses.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Coral fish condition, Pare-Pare Bay, Awerange Bay